Molecular detection of novel Anaplasma sp. and zoonotic hemopathogens in livestock and their hematophagous biting keds (genus Hippobosca) from Laisamis, northern Kenya [version 1; peer review: 3 approved] - Joel L. Bargul; Kevin O. Kidambasi; Daniel M. Mwaki; Kenneth Ogila; Jandouwe Villinger; Johnson Kinyua; Daniel K. Masiga; Dennis Getange; Collins Kigen; Mark Carrington (Open Research Africa)
Background: Livestock are key sources of livelihood among pastoral communities. Livestock productivity is chiefly constrained by pests and diseases. Due to inadequate disease surveillance in northern Kenya, little is known about pathogens circulating within livestock and the role of livestock-associated biting keds (genus Hippobosca) in disease transmission. We aimed to identify the prevalence of selected hemopathogens in livestock and their associated blood-feeding keds. Methods: We randomly collected 389 blood samples from goats (245), sheep (108), and donkeys (36), as well as 235 keds from both goats and sheep (116), donkeys (11), and dogs (108) in Laisamis, Marsabit County, northern Kenya. We screened all samples for selected hemopathogens by high-resolution melting (HRM) analysis and sequencing of PCR products amplified using primers specific to the genera: Anaplasma, Trypanosoma, Clostridium, Ehrlichia, Brucella, Theileria, and Babesia. Results: In goats, we detected Anaplasma ovis (84.5%), a novel Anaplasma sp. (11.8%), Trypanosoma vivax (7.3%), Ehrlichia canis (66.1%), and Theileria ovis (0.8%). We also detected A. ovis (93.5%), E. canis (22.2%), and T. ovis (38.9%) in sheep. In donkeys, we detected ‘Candidatus Anaplasma camelii’ (11.1%), T. vivax (22.2%), E. canis (25%), and Theileria equi (13.9%). In addition, keds carried the following pathogens; goat/sheep keds - T. vivax (29.3%), Trypanosoma evansi (0.86%), Trypanosoma godfreyi (0.86%), and E. canis (51.7%); donkey keds - T. vivax (18.2%) and E. canis (63.6%); and dog keds - T. vivax (15.7%), T. evansi (0.9%), Trypanosoma simiae (0.9%), E. canis (76%), Clostridium perfringens (46.3%), Bartonella schoenbuchensis (76%), and Brucella abortus (5.6%). Conclusions: We found that livestock and their associated ectoparasitic biting keds carry a number of infectious hemopathogens, including the zoonotic B. abortus. Dog keds harbored the most pathogens, suggesting dogs, which closely interact with livestock and humans, as key reservoirs of diseases in Laisamis. These findings can guide policy makers in disease control.